1986
DOI: 10.1007/bf00028599
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cytoplasmic male sterility in Petunia hybrida and Zea mays. Localization and activity of cytochrome c oxidase

Abstract: INDEX WORDSPetunia hybria'a, Zea mays, cytoplasmic male sterility, biochemical analysis, cytochemical analysis, cytochrome c oxidase. ABBREVIATIONS cox = cytochrome c oxidase; DAB = 3,3'-diaminobenzidine. SUMMARY Anthers ofmale fertile, cytoplasmic male sterile (ems), and restored male fertile Petunia hybridu, are analyzed for cytochrome c oxidase (cox) activity in subsequent stages of microsporogenesis, and compared with anthers of male fertile, ems-S and ems-C Zea mays. The cox activity is determined in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 26 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…No significant decrease in cytochrome c oxidase activity was observed during anther development in either the fertile or the sterile line, suggesting that the decrease in cytochrome c is not caused by downregulation of the cytochrome c oxidase pathway ( Figure 7B). In contrast, Bino et al (1986) observed a lower activity of cytochrome c oxidase in CMS petunia just after the onset of cellular degradation and in CMS-S maize before degeneration of the microspores compared with their respective isonuclear fertile lines. However, the enzyme activity measured reflects the maximum activity in the presence of excess cytochrome c substrate, which may not reflect the situation in vivo.…”
Section: Decrease In Mitochondrial Cytochrome C In Sterile Anthers Prmentioning
confidence: 59%
“…No significant decrease in cytochrome c oxidase activity was observed during anther development in either the fertile or the sterile line, suggesting that the decrease in cytochrome c is not caused by downregulation of the cytochrome c oxidase pathway ( Figure 7B). In contrast, Bino et al (1986) observed a lower activity of cytochrome c oxidase in CMS petunia just after the onset of cellular degradation and in CMS-S maize before degeneration of the microspores compared with their respective isonuclear fertile lines. However, the enzyme activity measured reflects the maximum activity in the presence of excess cytochrome c substrate, which may not reflect the situation in vivo.…”
Section: Decrease In Mitochondrial Cytochrome C In Sterile Anthers Prmentioning
confidence: 59%